EFFECT OF BIOFERTILIZER ON GROWTH AND NITROGEN UPTAKE OF SOYBEAN PLANTS (Glycine max. L.) VARIETIES MITANI AND ANJASMORO - Taufiq Bachtiar; Setiyo Hadi Waluyo (Widyariset, 2013)
Application for Rhizobium in local farmers has to be developed to support sustainable agriculture. This research was conducted to determine the influence of Rhizobium as a biofertilizer on growth and Nitrogen (N) uptake of two varieties of soybean. The experiment was carried out from January to May 2011 in South Jakarta. Randomized Block Design (RBD) was used in this experiment with six treatments and four replicates. The treatments were: K0=uninoculated with biofertilizer without urea, K100=uninoculated but with urea 100% equal 75 kg/ha, SS=inoculated with single strain biofertizer without urea, MS= inoculated with multi strain biofertilizer without urea, SS+50 =inoculated single strain biofertilizer with 50% urea, MS+50= inoculated multi strain biofertilizer with urea 50%. The results showed that application of MS +50 gave the best result on plant height, N uptake, nodule number and dry shoot of soybean plant varieties Mitani. Application of SS +50 gave the best results on plant height, N uptake, nodule number, and dry shoot of soybean plants varieties Anjasmoro.